Regulation of the Waqif Heirs in the Law of Waqf in Indonesia and Malaysia - Al-Anshori, Huzaimah; Ramadhita, Ramadhita; Manfaluthi, Agus (Journal of Law, Politic and Humanities, 2025)
Indonesia and Malaysia, as developing countries, have similarities and differences regarding the heirs of the waqif, from their implementation, legal basis, and system, to the resolution of waqf disputes. This investigation scrutinizes the convergences and divergences within the waqf juridical frameworks of Indonesia and Malaysia, with implications that enrich the global dialogue on waqf jurisprudence. The study adopts a doctrinal, literature-oriented methodology, employing a normative juridical paradigm and relying on secondary data comprising primary, secondary, and tertiary legal sources. The analytical technique employed is comparative in nature. The outcomes of this inquiry elucidate that the legal configuration governing the heirs of a waqif in both Indonesia and Malaysia embodies distinct attributes reflective of their respective sociocultural typologies. The legislative treatment of waqif heirs in the two jurisdictions diverges; in Indonesia, their recognition is expressly articulated in Article 6, paragraphs (2) and (4) of Government Regulation No. 42 of 2006, which operationalizes the Waqf Law. The existing nazir informs the waqif or the waqif heirs, and the waqif heirs have the right to propose to the Indonesian Waqf Board (BWI) for the nazir‘s termination and replacement. In Malaysia, the waqif heirs are not specifically regulated, but there is legislation stipulating that in the waqf practice, the waqif must obtain approval from the King and the waqif heirs. The common point between these two countries lies in the framework of Islamic law, which follows the Shafi'i madhhab but is not absolute. However, in Malaysia, this only applies in certain states.